2006
DOI: 10.1094/pd-90-0039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Severity Assessment Methods for Predicting Yield Loss to Rhizoctonia Foliar Blight in Soybean

Abstract: Rhizoctonia foliar blight, caused by Rhizoctonia solani Kühn anastomosis group 1, causes rapid and severe destruction of soybean foliage and pods during hot, wet weather. The objectives of this study were to determine the yield components affected by this disease and whether rating pod damage or foliar damage provides a more reliable method of assessing disease severity relative to impact on yield. Disease severity in the moderately resistant cv. NK S57-11 and the susceptible cv. Buckshot 723 was assessed in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Isolates of the R . solani AG1-IA complex can infect aerial portions of the plant as in the case of soybean leaves causing rhizocotnia foliar blight (RFB) [ 3 , 6 , 7 ]. The common elements in disease development of R .…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of the R . solani AG1-IA complex can infect aerial portions of the plant as in the case of soybean leaves causing rhizocotnia foliar blight (RFB) [ 3 , 6 , 7 ]. The common elements in disease development of R .…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of AG1-IA on soybean in Brazil, the southern states of the U.S.A. and China have caused yield losses of 30–60% [3, 4]. Protection against RFB is difficult as the use of less-susceptible cultivars is limited due to a lack of availability [1] resulting in the use of chemical pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoctonia foliar blight (RFB) caused by Rhizoctonia solani anastomosis group (AG) 1 intraspecific group IA is a serious disease that causes rapid and severe destruction of soybean ( Glycine max L. Merr) [ 1 , 2 ]. Outbreaks of AG1-IA on soybean in Brazil, the southern states of the U.S.A. and China have caused yield losses of 30–60% [ 3 , 4 ]. Protection against RFB is difficult as the use of less-susceptible cultivars is limited due to a lack of availability [ 1 ] resulting in the use of chemical pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, we set out to determine whether increasing amendment rates of maple bark biochar would produce similar results to what we previously reported on a soilborne pathogen, when soybean is subjected to a foliar pathogen belonging to the same taxonomic group, and whether plant and pathogen responsive genes are affected. Rhizoctonia foliar blight (RFB) of soybean, caused by R. solani AG1-IA can result in yield losses up to 60% (Fenille et al, 2002 ; Stetina et al, 2006 ) in Brazil and the southern states of the USA. Analysis of RNA sequencing of soybean-RFB interactions showed that plant genes involved in photosynthesis metabolic pathway were down-regulated with concomitant up-regulation of genes associated with amino acid and carbohydrate pathways and the tricarboxylic acid (TCA) cycle, presumably to provide energy, and carbon and nitrogen sources for secondary metabolism and defensive compounds (Copley et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%